Sea otter sunrise - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2025)
"It's bright and early when the magic tree house spins Jack and Annie to Monterey Bay, California. It's their mission to collect sea urchins in the underwater kelp forests! But they know nothing about collecting sea urchins -- can a grouchy boat captain help them? Maybe. But Jack and Annie have another problem when Annie finds a badly injured sea otter. They're not supposed to help the otter ... but it's the right thing to do. Can they convince the grouchy boat captain to help them?--